Newborn Screening for Pompe Disease in Illinois: Experience with 684,290 Infants - Barbara K. Burton; Joel Charrow; George E. Hoganson; Julie Fleischer; Dorothy K. Grange; Stephen R. Braddock; Lauren Hitchins; Rachel Hickey; Katherine M. Christensen; Daniel Groeppner; Heather Shryock; Pamela Smith; et al. (MDPI AG, 2020)
Statewide newborn screening for Pompe disease began in Illinois in 2015. As of 30 September 2019, a total of 684,290 infants had been screened and 395 infants (0.06%) were screen positive. A total of 29 cases of Pompe disease were identified (3 infantile, 26 late-onset). While many of the remainder were found to have normal alpha-glucosidase activity on the follow-up testing (234 of 395), other findings included 62 carriers, 39 infants with pseudodeficiency, and eight infants who could not be given a definitive diagnosis due to inconclusive follow-up testing.